Mobile Plasmid Mediated Transition From Colistin-Sensitive to Resistant Phenotype in Klebsiella pneumoniae - Zhang, Baoyue; Yu, Bing; Zhou, Wei; Wang, Yue; Sun, Ziyong; Wu, Xiaojun; Chen, Shiyun; Ni, Ming; Hu, Yangbo (Frontiers in Microbiology, 2021)
Multidrug-resistant bacteria, including carbapenem-resistant Klebsiella pneumoniae (CRKP), are becoming an increasing health crisis worldwide. For CRKP, colistin is regarded as “the last treatment option.” In this study, we isolated a clinical CRKP strain named as K. pneumoniae R10-341. Phenotyping analysis showed that this strain could transit from a colistin-sensitive to a resistant phenotype by inserting an IS4 family ISKpn72 element into the colistin-resistance associated mgrB gene. To investigate the mechanism of this transition, we performed genome sequencing analysis of the colistin-sensitive parental strain and found that 12 copies of ISKpn72 containing direct repeats (DR) are located on the chromosome and 1 copy without DR is located on a multidrug-resistant plasmid pR10-341_2. Both types of ISKpn72 could be inserted into the mgrB gene to cause colistin-resistance, though the plasmid-derived ISKpn72 without DR was in higher efficiency. Importantly, we demonstrated that colistin-sensitive K. pneumoniae strain transferred with the ISKpn72 element also obtained the ability to switch from colistin-sensitive to colistin-resistant phenotype. Furthermore, we confirmed that the ISKpn72-containing pR10-341_2 plasmid was able to conjugate, suggesting that the ability of causing colistin-resistant transition is transferable through common conjugation. Our results point to new challenges for both colistin-resistance detection and CRKP treatment.